Decarburization of wire-arc additively manufactured ER70S-6 steel - Aprilia, Aprilia (2023)
Decarburization is an unwanted carbon-loss phenomenon on the surfaces of a material when they are exposed to oxidizing environments at elevated temperatures. Decarburization of steels after heat treatment has been widely studied and reported. However, up to now, there has not been any systematic study on the decarburization of additively manufactured parts. Wire-arc additive manufacturing (WAAM) is an efficient additive manufacturing process for producing large engineering parts. As the parts produced by WAAM are usually large in size, the use of a vacuum environment to prevent decarburization is not always feasible. Therefore, there is a need to study the decarburization of WAAM-produced parts, especially after the heat treatment processes. This study investigated the decarburization of a WAAM-produced ER70S-6 steel using both the as-printed material and samples heat-treated at different temperatures (800 °C, 850 °C, 900 °C, and 950 °C) for different durations (30 min, 60 min, and 90 min). Furthermore, numerical simulation was carried out using Thermo-Calc computational software to predict the carbon concentration profiles of the steel during the heat treatment processes. Decarburization was found to occur not only in the heat-treated samples but also on the surfaces of the as-printed parts (despite the use of Ar for shielding). The decarburization depth was found to increase with an increase in heat treatment temperature or duration. The part heat-treated at the lowest temperature of 800 °C for merely 30 min was observed to have a large decarburization depth of about 200 μm. For the same heating duration of 30 min, an increase in temperature of 150 °C to 950 °C increased the decarburization depth drastically by 150% to 500 μm. This study serves well to demonstrate the need for further study to control or minimize decarburization for the purpose of ensuring the quality and reliability of additively manufactured engineering components.